Legal Aspects of Enlargement of the European Union - Varadi, Szilvia (LeXonomica, 2021)
The pulling power of the European Union has helped to transform Central and Eastern European countries into modern, well-functioning democracies. Regarding its integration activities, enlargement is one of the EU’s most powerful policy tools. This paper analyses the legal basis of the enlargement of the EU embodied in Art. 49 of the Treaty of the European Union, which is a result of an evolution lasting for nearly 70 years, but this evolution has not been finished, because there are still unclarified and open issues regarding the legal regulations. This paper overviews the accession criteria, finds that the enlargement process found in this Art. and in practice reveals some hiatuses of the legal basis of the enlargement and proposes to extend the enlargement clause with the basic procedural rules, fundamental principles and the conditions for membership developed in practice.Raztezna moč Evropske unije je pomagala preoblikovati države srednje in vzhodne Evrope v sodobne, dobro delujoče demokracije. Z integracijskega vidika je širitev eno najmočnejših orodij EU. Ta referat presoja pravno osnovo za širitev EU, ki je zajeta v členu 49 Pogodbe o Evropski uniji in je rezultat skoraj 70-letnega razvoja. Vendar pa ta razvoj ni dokončan, saj še zmeraj obstajajo nepojasnjena in odprta vprašanja pravne ureditve širitve. V članku avtorica obravnava pristopne kriterije, ugotovlja, da širitveni proces z omenjene določbe in iz prakse razkriva nekatera razhajanja med pravno osnovo za širitev ter predlaga razširitev širitvene klavzule z osnovnimi procesnimi pravili, temeljnimi načeli in pogoji za širitev, ki so se razvili v praksi.